Die Ablassdebatte auf dem Konzil von Trient - Maffeis, Angelo (Catholica <Münster>, 2024)
The decree on indulgences was only adopted on the eve of the conclusion of the Council of Trent, on 4 December 1563. 14 years earlier, after the Council had adjourned, the theologians gathered in Bologna had begun an extensive debate on the nature, basis and scope of indulgences. By reflecting on the origins and tradition of a long-standing ecclesiastical practice of indulgences, their legitimacy was to be established, in the end, the Council of Trent ruled only on the legality and usefulness of the practice for the faithful. The Council did not issue a comprehensive, binding statement on indulgences.